Petrological Geodynamics of Mantle Melting I. AlphaMELTS + Multiphase Flow: Dynamic Equilibrium Melting, Method and Results - Tirone, Massimiliano; Sessing, Jan (Frontiers in Earth Science, 2017)
The complex process of melting in the Earth's interior is studied by combining a multiphase numerical flow model with the program AlphaMELTS which provides a petrological description based on thermodynamic principles. The conceptual idea is based on a 1-D description of the melting process that occurs along a vertical ideal column where local chemical equilibrium is assumed to apply at some level in space and time. In this first installment of a series of three contributions, the focus is on a two-phase flow model (melt and solid assemblage) and complete local equilibrium between melt and a peridotitic mantle (dynamic equilibrium melting). The solid mantle is also assumed to be completely dry. The present study addresses some but not all the potential factors affecting melting. The influence of permeability and viscosity of the solid matrix are considered in some detail. Some effort is put to clearly present the essential features of the dynamic model and how it is interfaced with AlphaMELTS. The general observation that can be made from the outcome of many simulations carried out for this work is that the melt composition varies with depth, however the melt abundance non necessarily always increases moving upwards. When a quasi-steady state condition is achieved, that is when melt abundance does not varies with time, the melt composition approaches the composition that is obtained from a dynamic batch melting model which assumes the velocities of melt and residual solid to be the same. Time dependent melt fluctuations can be observed under certain conditions. In this case the composition of the melt that reaches the top side of the model (exit point) can vary to some extent. A consistent result of the model under various conditions is that the volume of the first melt that arrives at the exit point is substantially larger than any later melt outflux. The analogy with the large magma emplacement associated to continental break-up or formation of oceanic plateaus suggests that these events are the direct consequence of a dynamic two-phase flow process. Complete data files of most of the simulations are available in the supplementary material.